Mononuclear salen-gallium complexes for iso-selective ring-opening polymerization (ROP) of rac-lactide. Issue 38 (18th September 2017) - Specklin, David; Fliedel, Christophe; Hild, Frédéric; Mameri, Samir; Karmazin, Lydia; Bailly, Corinne; Dagorne, Samuel
Abstract : Mononuclear salen-supported Ga amido and alkoxide complexes, structurally characterized herein, mediate the controlled and iso-selective polymerization of rac -lactide. Abstract : A series of mononuclear salen-supported gallium amido/alkoxide derivatives were prepared and structurally characterized and subsequently used as initiators in rac -lactide ring-opening polymerisation (ROP). The reaction of variously substituted salen ligands (1a–1f ) with 0.5 equiv. of Ga2 (NMe2 )6 allowed the isolation of the corresponding (salen)Ga-NMe2 chelates (2b–2d, 2f ) via an amine elimination route, as poorly soluble compounds in common solvents. The (salen)Ga-OBn derivatives (3a–3e ) may be readily accessed by an amine-elimination/alcoholysis sequence and the molecular structures of3a, 3d and3e were confirmed through X-ray crystallography diffraction analysis. The present (salen)Ga-X species may effectively mediate the iso-selective ROP of rac -LA in a controlled manner ( P m up to 0.77 using a 1/12f /BnOH mixture as ROP initiator), with a ROP activity greatly dependent upon steric hindrance and geometrical constraints imposed by the variously substituted salen ligands. Based on the present study, salen ligands with limited steric hindrance and a certain degree of flexibility appear best suited for iso-selective ROP by (salen)Ga chelates. The salen-gallium complex3a is also effective for the controlled ROP of ε-caprolactone (CL) and the production of PCL- b -PLA copolymers.